Pengaruh Corporate Sosial Responsibility Dan Good Corporate Governace Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening (Pada Sektor Consumer Non-Cyclicals Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bei Tahun 2020-2024) - Meldawati . (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to determine the influence of corporate social responsibility and good corporate governance on firm value, with profitability as an intervening variable, in non-cyclical consumer sector companies. This study employed quantitative research with purposive sampling. The independent variables were corporate social responsibility and good corporate governance, while the dependent variable was firm value. Twenty-five companies served as the sample. Data were obtained from the financial reports published by each company on their official websites using SPSS 26. The results of this study are: (1) corporate social responsibility has a negative and significant effect on profitability; (2) good corporate governance has a negative and significant effect on profitability; (3) corporate social responsibility has a positive and significant effect on firm value; (4) good corporate governance has a negative and significant effect on firm value; (5) profitability has a positive and significant effect on firm value; (6) profitability does not mediate the effect of corporate social responsibility on firm value; (7) profitability does not mediate the effect of good corporate governance on firm value.